2007
DOI: 10.1007/s10725-007-9223-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthetic capacity and polypeptide patterns during natural senescence and rejuvenation of Cucurbita pepo L. (zucchini) cotyledons

Abstract: Natural senescence of Cucurbita pepo (zucchini) cotyledons was accompanied by a gradual degradation of reserve proteins (globulins) and an intensive decrease in the content of both large subunit (LSU) and small subunit (SSU) of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). The net photosynthetic rate, the primary photochemical activity of PSII, estimated by the variable fluorescence (F v )/maximal fluorescence (F m ) ratio (F v /F m ) and the actual quantum yield of PSII electron transport in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…As we aimed to investigate simultaneously the effect of darkness on both cotyledons and leaves, we used 14-day-old plants. Our recent results showed that the amount of reserve globulins in the cotyledons at that growth stage was significantly reduced (Ananieva et al 2008a), thus indicating that the mixotrophic metabolism typical for the early stages of cotyledon development had been changed to fully autotrophic characteristic for the true leaves (Kutik et al 1998). Thus, although cotyledons and leaves were not of the same age, they were characterized with similar physiological status.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As we aimed to investigate simultaneously the effect of darkness on both cotyledons and leaves, we used 14-day-old plants. Our recent results showed that the amount of reserve globulins in the cotyledons at that growth stage was significantly reduced (Ananieva et al 2008a), thus indicating that the mixotrophic metabolism typical for the early stages of cotyledon development had been changed to fully autotrophic characteristic for the true leaves (Kutik et al 1998). Thus, although cotyledons and leaves were not of the same age, they were characterized with similar physiological status.…”
Section: Discussionmentioning
confidence: 95%
“…The differences found in total chlorophyll content as well as in the life span between cotyledons and primary leaves can be interpreted in terms of the specific functions of cotyledons, being reserve organs during the early stages of germination which later function as photosynthesizing organs (La Rocca et al 1996;Kutik et al 1998;Ananieva et al 2008a). The timecourse changes in total chlorophyll content in zucchini cotyledons were in accordance with the progressive decline in the photosynthetic rate reported recently (Ananieva et al 2008a), thus ensuring their longer life span and slower senescence as compared to primary leaves. Moreover, the time of cotyledon death coincided with the formation of the 9th-10th differentiated leaves and the beginning of flowering, thus confirming the correlative control of their senescence (Lim et al 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have focused on characterizing age-dependent cotyledon senescence in different plant species, such as soybean, cucumber, cotton, and pumpkin (Bick and Strehler, 1971; Kanazawa et al , 2000; Xie et al , 2008; Ananieva et al , 2008 b ) and light irradiation accelerated cotyledon senescence (Watanabe et al , 1994; Wilhelmová et al , 2004). In this study, the phenotype of nitric oxide-induced cotyledon senescence was investigated and the nes1 mutant was characterized as having early cotyledon senescence which was induced by nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…The hop plant grows up to 8 m in height, resulting in the presence of leaves of different age on the plant. The leaves in the lower parts achieved photosynthetic maturity earlier than leaves in the upper parts of the hop plants, reaching senescence earlier, which results in a lower rate of gas exchange (Ananieva et al 2008). In the lower parts, the offshoot leaves were formed at a time when the hop plant had not yet reached its final height and the bine leaves were still unformed.…”
Section: Discussionmentioning
confidence: 99%